Determinants of productivity of Ukrainian firms - Andrzej Cieślik; Iryna Gauger; Jan Jakub Michałek (Comparative Economic Research. Central and Eastern Europe, 2017)
This paper examines the determinants of total factor productivity (TFP) of Ukrainian firms in manufacturing and services, using micro-level data for the years 2005 and 2013. We first estimate regressions for the pooled dataset for the manufacturing and service sectors jointly, and then separately for each sector. Our empirical results show a positive link between the total factor productivity, intangible assets, capital intensity, firm size, competition in the industry, ownership status, and firm internationalization (exports and imports). In addition, we find that the determinants of productivity differ among the sectors and years of our sample.
Keywords: 330; productivity; firms; Ukraine